2014
DOI: 10.1177/0898264314549662
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Diabetes Self-Efficacy and Psychological Distress Among Older Adults

Abstract: Objective This study examined racial/ethnic differences in the relationship between diabetes self-efficacy and psychological distress among older adults with diabetes mellitus. Method Adults aged 60 or older with a diagnosis of diabetes mellitus (N = 3,067) were drawn from the 2009 California Health Interview Survey (CHIS). Hierarchical multiple regression analyses were conducted. Results After controlling for covariates, African Americans and those with higher levels of diabetes self-efficacy tended to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The associations between changes in psychosocial factors and change in diabetes distress may have ethnic differences (Kim et al . ). This study need to be conducted on diverse ethnic groups in the future.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The associations between changes in psychosocial factors and change in diabetes distress may have ethnic differences (Kim et al . ). This study need to be conducted on diverse ethnic groups in the future.…”
Section: Discussionmentioning
confidence: 97%
“…A person who believes that he or she can lead a self‐determined life will experience less hopelessness and thus may experience less psychological distress (Kim et al . ). Cross‐sectional studies have reported a negative association between diabetes self‐efficacy and diabetes distress in patients with T2DM (Wardian & Sun , Kim et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies have examined the relationship between both social support (Condrasky, Baruth, Wilcox, & Carter, 2013; Shaya et al, 2013; Utz et al, 2008; Watkins, Quinn, Ruggiero, Quinn, & Choi, 2013) and self- efficacy (Al Sayah, Majumdar, Egede, & Johnson, 2015; Kim, Shim, Ford, & Baker, 2015; Peek et al, 2012; Peyrot et al, 2014; Steinhardt, Mamerow, Brown, & Jolly, 2009) and diabetes related outcomes. However, few studies have examined the relationship between social support and self-efficacy among AAs with diabetes (Heisler & Piette, 2005; Hunt, Grant, & Pritchard, 2012; Klug, Toobert, & Fogerty, 2008; Lorig, Ritter, Villa, & Armas, 2009).…”
Section: Introductionmentioning
confidence: 99%